Vulneración al derecho a una justa remuneración a los trabajadores del sector privado en Ecuador - Gaspar-Santos, Manacés Esaud; Cruz-Gálvez, Klever Javier; Marín-Vilela, Lady Sadith; Mendoza-Arce, Kahyner Yuleydi (IUSTITIA SOCIALIS, 2021)
Vulneración al derecho a una justa remuneración a los trabajadores del sector privado en Ecuador